Pembentukan Portofolio Optimal Saham Syariah yang Terdaftar di JII dengan Metode Single Index Model - Sukma Febrianti; Marjono Marjono; Tia Apriani (Jurnal Ilmiah Ekonomi Islam, 2021)
Sharia stocks showed better performance than conventional stocks with more stable returns. The purpose of this research is to compile an optimal portfolio of Shariah stocks listed on JII in order to generate higher returns using the single index model method. The study used 17 companies sampled with purposive sampling techniques, data used is monthly stock price, IHSG and BI rate. Based on the results of obtained by 5 companies included in the optimal portfolio, PT Indofood CBP Sukses Makmur Tbk with a proportion of funds of 59.93%, PT Vale Indonesia Tbk with a proportion of funds of 16.16%, PT. Semen Indonesia Tbk with a proportion of funds of 16.05%, PT Bukit Asam Tbk with a proportion of funds of 6.29% and a proportion of funds of 1.56% in the company PT Aneka Tambang Tbk. From the results of the calculation of returns and risks showed that the portfolio provides a higher profit than the market return.